Changing Scenario of Purchasing Pattern and the Utilization of Department Stores - Manivannan, L.; Raghunathan, P.N (Indian Journal of Marketing, 2004)
Purchasing is an art, and those who lack in it are likely to get a lot of confusion during the time of purchase and during making purchase decisions. Department stores make shopping attractive and agreeable. The service providers at department stores may station at strategic points and attenders may guide the customers to the concerned departments. Trained salesmen, who are courteous and tactful and who can convince the consumers may be employed. Recreation facilities in the form of music programmes, movie pictures, magic shows etc., may also be arranged A lounge, a restaurant, an Ice-cream parlour, reading and writing rooms, Telephone booths, beauty clinics, a nursery to care for small children, lectures, demonstrations, free classes in Ikebana and other arts (arts and handicraft), fashion shows, exhibitions may also be arranged. These facilities and services go to create a "home image" for the department store concerned. They can also allow credit, take orders on telephone, offer home delivery, and provide gift-wrapping, exchange of unsatisfactory goods and refunding of money in case of dissatisfaction.